Evaluation of learning process: Knowledge of ICT integration among pre-service English language teachers - Dyah Setyowati Ciptaningrum; Nur Hidayanto Pancoro Setyo Putro; Nila Kurnia Sari; Nurqadriyanti Hasanuddin (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2021)
This research aims at investigating the knowledge of ICT integration among the students of the English Language Education Study Program at a particular university in Yogyakarta. By employing the quantitative method, this ex-post facto research involved 70 English Department students who had taken microteaching as respondents in a survey to gather the data using a questionnaire. The questionnaire was taken from the model developed by one of the researchers based on the TPACK framework. There are five domains in the questionnaire. Four domains measure TPACK perceptions: Technological Knowledge (TK), Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK), and Technological Pedagogical Content Knowledge (TPACK). One domain measures the pre-service teachers’ perceptions of their ICT-related learning experiences. Demographic questions are included to identify the characteristics of the respondents in order to understand gender differences or relationships between teachers who have access to technologies at home and those who do not. The closed-ended questions applied a five-point Likert-type scale ranging from 1=strongly disagree to 5=strongly agree. Correspondingly, it contains one open-ended question in the TPACK domain. Descriptive analysis and MANOVA were conducted for the quantitative data analysis. The result of this study showed that the pre-service students possess a high self-confidence in the application of TK (Technological Knowledge), TPK (Technological Pedagogical Knowledge), and TCK (Technological Content Knowledge). However, their TPACK appears to need further development. The results from MANOVA showed that the pre-service teachers’ related learning experiences significantly differed by the students’ gender, with male students reporting more experiences than female students.